CONTROLS ON FE REDUCTION AND MINERAL FORMATION BY A SUBSURFACE BACTERIUM - Glasauer S.; Weidler P.G.; Langley S.; Beveridge T.J. (My University, 2003)
The reductive dissolution of FeIII (hydr)oxides by dissimilatory iron-reducing bacteria (DIRB) could have a large impact on sediment genesis and Fe transport. If DIRB are able to reduce FeIII in minerals of high structural order to carry out anaerobic respiration, their range could encompass virtually every O2-free environment containing FeIII and adequate conditions for cell growth. Previous studies have established that Shewanella putrefaciens CN32, a known DIRB, will reduce crystalline Fe oxides when initially grown at high densities in a nutrient-rich broth, conditions that poorly model the environments where CN32 is found. By contrast, we grew CN32 by batch culture solely in a minimal growth medium. The stringent conditions imposed by the growth method better represent the conditions that cells are likely to encounter in their natural habitat. Furthermore, the expression of reductases necessary to carry out dissimilatory Fe reduction depends on the method of growth. It was found that under anaerobic conditions CN32 reduced hydrous ferric oxide (HFO), a poorly crystalline FeIII mineral, and did not reduce suspensions containing 4 mM FeIII in the form of poorly ordered nanometer-sized goethite (α-FeOOH), well-ordered micron-sized goethite, or nanometer-sized hematite (α-Fe2O3) crystallites. Transmission electron microscopy (TEM) showed that all minerals but the micron-sized goethite attached extensively to the bacteria and appeared to penetrate the outer cellular membrane. In the treatment with HFO, new FeII and FeIII minerals formed during reduction of HFO-Fe in culture medium containing 4.0 mmol/L Pi (soluble inorganic P), as observed by TEM with energy-dispersive X-ray spectroscopy, selected area electron diffraction, and X-ray diffraction. The minerals included magnetite (Fe3O4), goethite, green rust, and vivianite [Fe3(PO4)2 . 8H2O]. Vivianite appeared to be the stable end product and the mean coherence length was influenced by the rate of FeIII reduction. When Pi was 0.4 mol/L under otherwise identical conditions, goethite was the only mineral observed to form, and less Fe2+ was produced overall. Hence, the ability of DIRB to reduce Fe (hydr)oxides may be limited when the bacteria are grown under nutrient-limited conditions, and the minerals that result depend on the vigor of FeIII reduction.